2015
DOI: 10.1016/j.ejca.2014.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of herpesvirus entry mediator expression in human hepatocellular carcinoma

Abstract: Tumour-expressing HVEM plays a critical role in human HCC, possibly through regulating immune evasion. Therefore, targeting HVEM may be a novel promising therapeutic strategy for HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 40 publications
3
46
0
Order By: Relevance
“…HVEM also exists as a soluble form in the circulation . Preclinical and clinical studies have suggested that dysregulation of the HVEM network contributes to multiple inflammatory and infectious diseases . Currently, the expression pattern and roles of the HVEM axis in AH pathogenesis are unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HVEM also exists as a soluble form in the circulation . Preclinical and clinical studies have suggested that dysregulation of the HVEM network contributes to multiple inflammatory and infectious diseases . Currently, the expression pattern and roles of the HVEM axis in AH pathogenesis are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…(34) Preclinical and clinical studies have suggested that dysregulation of the HVEM network contributes to multiple inflammatory and infectious diseases. (33,(35)(36)(37) Currently, the expression pattern and roles of the HVEM axis in AH pathogenesis are unknown. Here, we found that expression of both soluble and membrane forms of the HVEM network were highly dysregulated in patients with AH.…”
Section: Discussionmentioning
confidence: 99%
“…We analyzed the impact of TIL to predict the outcome of patients with HBV‐positive or NBNC hepatitis, and find a significant association between high TIL and good OS, and low recurrence rate. To evaluate just TIL from HE staining is very easy and is able to be carried out in almost all hospitals; also the TIL count should be reproducible, accurate, and objective . The TIL count can assess preoperatively from biopsy specimens, and can used to decide the treatment strategy.…”
Section: Discussionmentioning
confidence: 99%
“…By ligation of LIGHT, HVEM stimulates T-cell responses, while binding to BTLA or CD160 leads to inhibition of T-cells. HVEM is known to be expressed in melanoma 29 and most recently in HCC 30 . IDO is the rate-limiting enzyme in the catabolism of the essential amino-acid tryptophan 31 .…”
Section: Introductionmentioning
confidence: 99%